2001
DOI: 10.1007/s004410100444
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous expression of acetylcholinesterase affects proliferation and glial cytoskeleton of adherent chicken retinal cells

Abstract: Besides its function at cholinergic synapses, acetylcholinesterase (AChE) exerts structural functions on neural differentiation, independent of its enzymatic activity. To elucidate such functions, we have previously heterologously expressed AChE in histotypic retinal reaggregates, revealing strong effects on their histogenesis, particularly on Müller glia processes. To further resolve these findings at a less complex cellular level, in this study we transfected adherent retinal cells of the chick embryo after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…5E), T‐1 being nearly three times larger (2437 ± 78 µm 2 ) than parental cells (873 ± 69 µm 2 ), and often extend long AChE‐rich processes over other cells (not shown). Elevation of AChE‐T expression in glioma, neuroblastoma and glial cells also increased cell body size and process extension (Karpel et al, 1996; Bigbee et al, 2000; Keller et al, 2001). A comparison of AChE catalytic activity in parental and AChE‐T‐overexpressing 3T3 clones T‐1 and T‐3 with that of neuronal PC12 cells, in the absence and presence of BW284c51 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5E), T‐1 being nearly three times larger (2437 ± 78 µm 2 ) than parental cells (873 ± 69 µm 2 ), and often extend long AChE‐rich processes over other cells (not shown). Elevation of AChE‐T expression in glioma, neuroblastoma and glial cells also increased cell body size and process extension (Karpel et al, 1996; Bigbee et al, 2000; Keller et al, 2001). A comparison of AChE catalytic activity in parental and AChE‐T‐overexpressing 3T3 clones T‐1 and T‐3 with that of neuronal PC12 cells, in the absence and presence of BW284c51 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings showed that the increased activity observed after iron exposure is not a consequence of increased AChE transcript levels. In this sense, it was already demonstrated that AChE from other sources was clearly regulated by a posttranslational event (Robitzki et al 1997;Keller et al 2001).…”
Section: Discussionmentioning
confidence: 93%
“…There were many reports on recombinant AChE. Researchers have cloned AChE cDNA from a variety of organisms, such as fish, Drosophila, chicken, snake, mouse, and nematode, and expressed it exogenously using various expression systems.…”
Section: Trends and Applications Of Emerging Technologies For Enzyme ...mentioning
confidence: 99%